Nitrate leaching and soil nitrous oxide emissions diminish with time in a hybrid poplar short‐rotation coppice in southern Germany - Díaz Pinés, Eugenio; Molina Herrera, S.; Dannenmann, Michael; Braun, J.; Haas, E.; Willibald, G.; Arias Navarro, Cristina; Grote, R.; Wolf, B.; Saiz, Gustavo; Aust, C.; Schnitzler, J.P.; et al. (Wiley, 2017)
Hybrid poplar short‐rotation coppices (SRC) provide feedstocks for bioenergy production and can be established on lands that are suboptimal for food production. The environmental consequences of deploying this production system on marginal agricultural land need to be evaluated, including the investigation of common management practices i.e., fertilization and irrigation. In this work, we evaluated (1) the soil‐atmosphere exchange of carbon dioxide, methane, and nitrous oxide (N2O); (2) the changes in soil organic carbon (SOC) stocks; (3) the gross ammonification and nitrification rates; and (4) the nitrate leaching as affected by the establishment of a hybrid poplar SRC on a marginal agricultural land in southern Germany. Our study covered one 3‐year rotation period and 2 years after the first coppicing. We combined field and laboratory experiments with modeling. The soil N2O emissions decreased from 2.2 kg N2O‐N ha−1 a−1 in the year of SRC establishment to 1.1–1.4 kg N2O‐N ha−1 a−1 after 4 years. Likewise, nitrate leaching reduced from 13 to 1.5–8 kg N ha−1 a−1. Tree coppicing induced a brief pulse of soil N2O flux and marginal effects on gross N turnover rates. Overall, the N losses diminished within 4 years by 80% without fertilization (irrespective of irrigation) and by 40% when 40–50 kg N ha−1 a−1 were applied. Enhanced N losses due to fertilization and the minor effect of fertilization and irrigation on tree growth discourage its use during the first rotation period after SRC establishment. A SOC accrual rate of 0.4 Mg C ha−1 a−1 (uppermost 25 cm, P = 0.2) was observed 5 years after the SRC establishment. Overall, our data suggest that SRC cultivation on marginal agricultural land in the region is a promising option for increasing the share of renewable energy sources due to its net positive environmental effects.